EFFECT OF EXTENDERS AND GLYCEROLIZATION PROCEDURES ON SOME CHARACTERISTICS OF FROZEN BULL SEMEN - I. Al-Badry ‎, Karem.; W. Al-Douri , Towfiq.; H. Ali, Hussin (The Iraqi Journal of Veterinary Medicine, 1988)
This study was carried out in Artificial Insemination Depart-cat / Abu-Ghraib on Friesian bulls born in Iraq. Twenty-four ejaculates were used in two experiments to study the suitability of three proceduresof adding glycerol namely "G1, G2 and G3" to extenders “TYC, TYFG, SMYLG and Laci", The results of this study could be summarized as follows:-a. Interaction between extender and type of adding glycerol was significant in some characteristics.b. The type two of adding glycerol "G2" had had results in extenders on Frozen semen characteristics.c. No significant difference between the two type of adding glycerol "Gi and G3 ", but G3 had good results more than Gi in SMYLQ extender. So the type on G1 of adding glycerol was suitability if used type one G1 of adding glyserol was suitability if used "TYG, TYFG and Laci" extenders. And type three G2 if used SMYLG extender.